3(c-63)=27

Simple and best practice solution for 3(c-63)=27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(c-63)=27 equation:


Simplifying
3(c + -63) = 27

Reorder the terms:
3(-63 + c) = 27
(-63 * 3 + c * 3) = 27
(-189 + 3c) = 27

Solving
-189 + 3c = 27

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '189' to each side of the equation.
-189 + 189 + 3c = 27 + 189

Combine like terms: -189 + 189 = 0
0 + 3c = 27 + 189
3c = 27 + 189

Combine like terms: 27 + 189 = 216
3c = 216

Divide each side by '3'.
c = 72

Simplifying
c = 72

See similar equations:

| 5x-9+3x=87 | | f(5)=3x+x^2 | | (X-2)/10=(x-7)/5 | | X+325=520 | | f(x)=3x+x^2 | | 4x+10-2x=-10 | | 3(k+9)=72 | | -t+-6=-10 | | 32(x-1)+115x+10(x+2)=1607 | | -24=8(r+63) | | 43=2x+2x+7 | | 3/7x3 | | 3h+2=-4 | | -2x-2+5x=16 | | 4(b-73)+44=60 | | 7-3m=13-5m | | p=15x-1000 | | 20=5+3m | | -4x+9+6x=23 | | (3x)/5=6/1 | | 10-2b^2=-88 | | 3x+8+3x=68 | | -2(k+5)=-4 | | 4(x+10)-7x=-2(x-13) | | 8=6+2u | | 3x+2=x^2-25 | | X^2+9=14 | | 5x+4+x=-14 | | X^2-3=25 | | 7n^2-3=445 | | 13-s=8 | | 2/3(n-(5/6))=2.5 |

Equations solver categories